INTERNALISASI NILAI-NILAI MODERASI BERAGAMA PADA GENERASI Z MELALUI PENGUATAN PENDIDIKAN KARAKTER (PPK) DI SEKOLAH (Penelitian di SMAN 5 Bandung) - Iwan Sanusi; Giantomi Muhammad; Ade Een Khaeruniah; Ulvah Nuraeni (At Turots: Jurnal Pendidikan Islam, 2024)
As social and religious beings, humans have life goals which are full of happiness and not the other way around. The influence of globalization, modernization, and the era of super information is a challenge for every citizen of the world, especially the pluralistic Indonesia. On one hand, the diversity is a gift from the God to be grateful for, but on the other hand it has some impacts such as disintegration, intolerance, the emergence of radicalism, fundamentalism, and extremism in society, especially in the zillennial generation. Therefore, there needs to be an in-depth study of the internalization of religious moderation values ​​as a solution for the zillennial generation in schools. Thus, the study in this research employed a qualitative research type with a descriptive-analytic approach that tried to explore the problem so that a solution is found, either theoretically or with the findings in the field. The results showed that in the process of implementing the values ​​of religious moderation in schools which include the values ​​of national commitment, tolerance, anti-violence, and being accommodative to local culture and its derivative values, was carried out through the Strengthening of School Character Education strategy based on the classroom learning, the school’s culture , and cooperation with the communities through the social media and the existence of religious Islamic Club extracurricular activity. The pillar model for developing the character values ​​of religious moderation was carried out through teaching, habituation, example, motivating, and enforcing rules that were integrated into the school's Character Education Strengthening program strategy.